Evaluasi Sistem Pengendalian Intern Atas Penjualan Kredit, Piutang dan Penerimaan Kas pada Pt Equipindo Perkasa: Studi Kasus pada Cabang Jakarta - Kriswanto, Kriswanto (Bina Nusantara University, 2011)
Selling is the main income for companies, therefore it needs selling internal control. The research method used is exploratory; it is used through literature review and field research. In gathering secondary data, the researcher used both theoretical and company documentation by gathering, reading and learning data and information theoretically. Meanwhile, in field research, the researcher explored company in direct as research object through observation, interview, and survey by questionnaire. The research result showed that internal control in selling function still has not properly executed. Through the existing problems, it could be concluded that internal control for credit selling has not executed effectively and efficiently.